固体燃料的气化系统 (2017)
本发明提供种使用褐煤等高水分的固体燃料的气化系统，其能够抑制由燃料干燥引起的能效降低以及有效利用燃料干燥所产生的水蒸气。使水分含有量较多的固体燃料在气化炉的上游侧干燥。在气化炉中供给干燥后的固体燃料，防止气化炉内的温度降低。另方面，将由燃料干燥产生的、含有水蒸气的气体向气化炉的下游供给，对生成气体进行冷却，促进变换反应。燃料干燥的热源使用由变换反应器下游的热回收产生的水蒸气、在由CO再生塔进行CO吸收液的再生加热中使用的水蒸气等设备废热、从生成气体回收后进行隔热压缩的CO等。 An object is to suppress energy efficiency reduction due to fuel drying and to effectively utilize steam generated through fuel drying in a gasification system using lignite or 5 another high-moisture solid fuel. A high-moisture solid fuel having a high moisture content is dried upstream from a gasifier. The high-moisture solid fuel after drying is fed to the gasifier to thereby prevent temperature fall in the gasifier. A steam-containing gas evolved through fuel drying is fed to 10 downstream from the gasifier, cools the syngas, and accelerates the shift reaction. Examples of the fuel-drying heat source include steam generated through heat recovery downstream from the shift reactor; plant exhaust heat derived typically from steam used for regenerative heating of a CO 2 15